2013
DOI: 10.1194/jlr.m042481
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular COX-2/mPGES-1/EP-4 axis in human abdominal aortic aneurysm

Abstract: Abdominal aortic aneurysm (AAA) is a late-age onset disorder that affects a high percentage of the population in industrialized countries, and rupture of AAA is associated with high mortality rates ( 1 ). The etiology of AAA is complex with a relevant contribution of genetic factors ( 2 ). Although much effort has been made to clarify the mechanism of AAA development, currently the only effective approach to prevent aneurysm rupture is surgical repair by conventional or endovascular techniques.Evidence has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 39 publications
6
54
1
2
Order By: Relevance
“…This was also supported by the action of the more specific EP‐4 antagonist CJ42794, which significantly inhibited cPGI 2 ‐induced in vitro angiogenesis. We have previously reported that PGE 2 ‐induced in vitro angiogenesis was mainly dependent on the EP‐4 receptor in ECs . Our results do not rule out the possibility that other prostanoid receptors could also be involved and we have no direct evidence of PGI 2 binding to EP‐4.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…This was also supported by the action of the more specific EP‐4 antagonist CJ42794, which significantly inhibited cPGI 2 ‐induced in vitro angiogenesis. We have previously reported that PGE 2 ‐induced in vitro angiogenesis was mainly dependent on the EP‐4 receptor in ECs . Our results do not rule out the possibility that other prostanoid receptors could also be involved and we have no direct evidence of PGI 2 binding to EP‐4.…”
Section: Discussioncontrasting
confidence: 84%
“…None of these antagonists modified the effect of cPGI 2 on in vitro angiogenesis (Figure B), indicating that neither IP nor PPARδ mediated the effect of cPGI 2 in HUVEC tube formation. We have previously reported that PGE 2 ‐induced angiogenesis in vitro was mainly dependent on the EP‐4 receptor in ECs . Other authors have also reported that PGI 2 produces biological activities through EP‐4 activation .…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…It has been reported that COX‐2 activity and expression maybe play a primary role in the formation and expansion of AAA . Compared to health donors, COX‐2 expression is obviously increased in AAA patients . On the contrary, the inhibition of COX‐2 depressed the increased vasoconstrictor response and endothelial dysfunction induced by Ang II infusion .…”
Section: Discussionmentioning
confidence: 98%
“…Prostaglandin E 2 (PGE 2 ) is associated with human cardiovascular 1, 2 and cerebrovascular disease 3 . PGE 2 also is involved in the pathogenesis of several animal models of cardiovascular 46 and cerebrovascular disease 7, 8 .…”
Section: Introductionmentioning
confidence: 99%